Content Analysis Of The Al-Arabiyyah Lil ‘Alam Educational Series Based On Gardner's Theory Of Multiple Intelligences - Pasandi, Faezeh; Hosein Abadi, Safoura Ghadami (Ijaz Arabi Journal of Arabic Learning, 2025)
According to modern educational theories, organized intelligences are key to effective learning and practical second language instruction. Howard Gardner's "Theory of Multiple Intelligences" is one of the most prominent. The five-volume series "Al-Arabiyyah lil-'Aalam" is a significant resource for Arabic language instruction worldwide. This study evaluates the content of this series based on the comprehensive text analysis method, applying Gardner's theory. Based on a statistical sample of 985 instances, the findings indicate that the highest frequency (540 cases of intelligence) was found in the exercises section, identified as this series's primary unit of analysis. The results of the research suggest that the "Al-Arabiyyah lil-'Aalam" series, through a novel and creative approach, utilizes nine of Gardner's intelligences to enhance and improve the four language skills, making it a suitable and practical resource for teaching Arabic to non-Arabic speakers.